Energetically and ecologically sustainable, affordable and healthy built environment - Lill, Irene (International Journal of Strategic Property Management, 2018)
Energetically and ecologically sustainable, affordable and healthy built environment. International Journal of Strategic Property Management, 22(4), p. 234-235.